Bereicherung und Schadenersatz im Immaterialgüterrecht Ein Beitrag zum Verhältnis zwischen Sonderprivatrecht und allemeinem Zivilrecht - Schacherreiter, Judith (Jan Sramek Verlag, 2018)
The special rules on unjust enrichment and damages in intellectual property law are subject of a discussion where representatives of civil law criticise them as incoherent in the general system of civil law and representatives of intellectual property law justify this incoherence with their practical utility. This book shows that it is important to bring general civil law in dialogue with the rules of "special private law" in order to link practical utility and theoretical coherence and to realize pragmatic solutions for certain cases within the frame of a coherent legal system.